Pharmacokinetic considerations for use of artemisinin-based combination therapies against falciparum malaria in different ethnic populations. (2nd November 2017) - Sugiarto, Sri Riyati; Davis, Timothy M. E.; Salman, Sam
ABSTRACT: Introduction : Artemisinin-based combination therapy (ACT) is used extensively as first-line treatment for uncomplicated falciparum malaria. There has been no rigorous assessment of the potential for racial/ethnic differences in the pharmacokinetic properties of ACTs that might influence their efficacy. Areas covered : A comprehensive literature search was performed that identified 72 publications in which the geographical origin of the patients could be ascertained and the key pharmacokinetic parameters maximum drug concentration (Cmax ), area under the plasma concentration-time curve (AUC) and elimination half-life (t½β ) were available for one or more of the five WHO-recommended ACTs (artemether-lumefantrine, artesunate-amodiaquine, artesunate-mefloquine, dihydroartemisinin-piperaquine and artesunate-sulfadoxine-pyrimethamine). Comparisons of each of the three pharmacokinetic parameters of interest were made by drug (artemisinin derivative and long half-life partner), race/ethnicity (African, Asian, Caucasian, Melanesian, South American) and patient categories based on age and pregnancy status. Expert opinion : The review identified no evidence of a clinically significant influence of race/ethnicity on the pharmacokinetic properties of the nine component drugs in the five ACTs currently recommended by WHO for first-line treatment of uncomplicated falciparum malaria. This provides reassurance for health workers in malaria-endemic regions that ACTs can be given in recommended doses with the expectation of adequate blood concentrations regardless of race/ethnicity.